Targeted delivery of immunotoxin by antibody to ganglioside GD3: a novel drug delivery route for tumor cells - Torres Demichelis, Vanina Andrea (2013)
Gangliosides are sialic acid-containing glycolipids expressed on plasma membranes from nearly all vertebrate cells. The expression of ganglioside GD3, which plays essential roles in normal brain development, decreases in adults but is up regulated in neuroectodermal and epithelial derived cancers. R24 antibody, directed against ganglioside GD3, is a validated tumor target which is specifically endocytosed and accumulated in endosomes. Here, we exploit the internalization feature of the R24 antibody for the selective delivery of saporin, a ribosome-inactivating protein, to GD3-expressing cells [human (SK-Mel-28) and mouse (B16) melanoma cells and Chinese hamster ovary (CHO)-K1 cells]. This immunotoxin showed a specific cytotoxicity on tumor cells grew on 2D monolayers, which was further evident by the lack of any effect on GD3-negative cells. To estimate the potential antitumor activity of R24-saporin complex, we also evaluated the effect of the immunotoxin on the clonogenic growth of SK-Mel-28 and CHO-K1GD3+ cells cultured in attachment-free conditions. A drastic growth inhibition (.80?90%) of the cell colonies was reached after 3 days of immunotoxin treatment. By the contrary, colonies continue to growth at the same concentration of the immuntoxin, but in the absence of R24 antibody, or in the absence of both immunotoxin and R24, undoubtedly indicating the specificity of the effect observed. Thus, the ganglioside GD3 emerge as a novel and attractive class of cell surface molecule for targeted delivery of cytotoxic agents and, therefore, provides a rationale for future therapeutic intervention in cancer.